Perancangan Sistem Informasi Data Pegawai Berbasis Web Pada PT.Sinar Halomoan - Hasibuan, Novrisyah; Ikhwan, Ali (Journal of Computer Science and Informatics Engineering, 2024)
Flowmap is a mixture of map and flow chart, Flowmap describes what activities are currently running. explain the relationships of data and information with the parts of the activity. With a flowmap, you can describe system entities in detail. At PT. Sinar Halomoan lack of employee data management. Usually the system used to manage data and store employee data is currently still using MS.Excel so it is not used optimally. So far, in the process of managing employee data, they still use Microsoft Office Excel, to obtain or access employee data, they must find the section that manages the data. In order to make this easier so that it does not become a problem for the company in the future, a web-based personnel information system is designed with boostrap version 4.5 so that this system can meet the needs of PT. Sinar Halomoan in terms of employee data collection. With the design of the employee data information system at PT. Sinar Halomoan, it is hoped that it will help the Personnel and HRD departments to facilitate the management of employee data.